Forage Properties of Fresh and Composted Cotton Gin Byproducts as Feed Supplements - Femi Peter Alege; Sean Paul Donohoe; Jaya Shankar Tumuluru; Christopher D. Delhom; Cody D. Blake; Joe W. Thomas (AgriEngineering, 2023)
Cotton ginning generates millions of tons of byproducts every year. If not properly managed, these materials become waste, which may constitute significant environmental, economic, and logistical issues. The objectives of this study were to characterize fresh and composted cotton gin byproducts (CGBs) for utilization as animal feed supplements and investigate the effects of composting on the forage properties. The study analyzed and compared the nutrients and energy contents of fresh and composted CGB from four commercial cotton gins in Arkansas, Mississippi, Missouri, and Tennessee states, USA. The results suggest that composting CGB may result in more than a 47% increase in fiber and crude protein and at least a 25% decrease in total digestible nutrients and net energy estimations. The differences in macro- and micro-nutrient contents and feed properties suggest that composting CGB may improve the potential for utilization as an animal feed supplement. Establishing the forage properties of CGB is crucial for determining animal feed formulations using CGB as supplements.